2014
DOI: 10.1021/jp4120783
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Ion–Graphene Electrode Interactions by Ionic Liquids: The Effects of Liquid Structure

Abstract: We have investigated the screening of solute ion−electrode interactions in two ionic liquids (1-butyl 3-methylimidazolium tetrafluoroborate [BMIm][BF 4 ] and 1,3dimethylimidazolium chloride [MMIm]Cl) by constructing free energy profiles for dissolved charged probes as a function of distance from a charged surface (graphene). The free energy profiles for three types of mutual interactions (surface and solute with opposite charges, solute and uncharged surface, and surface and solute with the same charges) diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 100 publications
2
67
1
1
Order By: Relevance
“…The simulation setups (equilibration, length of simulations, system parameters and computational methods) were overall the same to the ones used in our previous works: Ref. [20] (fully atomistic model of [BMIm][BF 4 ]) and Refs. [11] (coarse-grained models).…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation setups (equilibration, length of simulations, system parameters and computational methods) were overall the same to the ones used in our previous works: Ref. [20] (fully atomistic model of [BMIm][BF 4 ]) and Refs. [11] (coarse-grained models).…”
Section: Simulationsmentioning
confidence: 99%
“…The OPLS-AA force field was used together with partial charges taken from [22] for the IL. The charges were screened by a factor of 0.79 to account for the highfrequency electronic polarisability [20].…”
Section: Coarse-grained Simulationsmentioning
confidence: 99%
“…It is known that the performance of supercapacitors with ILs as the electrolyte depends on the IL functional group, and the selection of the cations and anions by varying the alkyl chain length 17,18. Various synthetic strategies have been reported for tailoring of the chemical structures of the IL cation or anion with different functional groups 19. Shaikh et al reported a simple Brønsted acidic ionic liquid as an electrolyte with Ru‐doped CuO thin‐film electrode, which demonstrated a potential window of 1.0 V, specific capacitance of 406 F g –1 , and retained this with cycle stability up to 2000 cycles 20.…”
Section: Introductionmentioning
confidence: 99%
“…For a deeper insight into the structure–reactivity correlation, detailed data on the molecular‐scale interface structure and dynamics at metal/RTILs interfaces is necessary, which is a subject of substantial current research 2d. 3 Recent experimental4 and theoretical studies3c, 5 revealed a multilayer architecture that exhibits fundamental differences compared to the electrochemical double layers found in aqueous and organic electrolytes.…”
mentioning
confidence: 99%